EXPRESSION OF THE PERSONALITY SPIRITUALITY IN THE CHARACTERS’ SPEECH - Abdullayev Xamro Dauletbaevich; Duysenbaev Olimjon Ismailovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the psychological functions of artistic discourse in the novels "Muvozanat" and "Rebellion and Obedience" by well-known Uzbek writer Ulugbek Hamdam. The article outlines the writer’s ability to create character, the lighting of religious issues, the unity of images and content, and the superstition of modern personality spirituality.